Wound care - A teaching topic with potential Wundversorgung - ein Lehrthema mit Potenzial - Erfurt-Berge, Cornelia (Aktuelle Dermatologie, 2024)
The treatment of patients with chronic wounds is part of basic dermatological care. The prevalence of chronic wounds increases with age and a rise in the number of patients can be expected in the future. At the same time, the topic of wound management is a prime example of interdisciplinary and interprofessional patient care and can therefore be followed up as a teaching topic in many medical disciplines. The student working as a general physician in the future will later take on the role of a pilot and must be able to refer the patient to the necessary specialties for diagnosis and treatment within a reasonable period of time. Having to deal with chronic wounds as a comorbidity can occur in any specialist discipline. In the field of wound management, dermatology not only covers the phlebological diagnostic, but also plays a key role in the diagnosis of rare causes of chronic wounds. The indication and performance of further diagnostics, such as a histological examination of a deep tissue sample, can be part of a learning unit for many dermatological diseases that present with ulceration as a symptom. There are therefore many didactic possibilities for integrating this topic into a teaching unit. In addition to cognitive learning objectives on the pathophysiology and differential diagnosis of chronic wounds, practical skills such as the application of dressings, sonography or debridement procedures can be taught. Affective learning objectives can also be integrated into curricula concerning the care for people with chronic illnesses or implementation of preventative measures.
CRIS-Team Scopus Importer:2025-04-01
Keywords: chronic wound; leg ulcer; venous insufficiency; wound managemenet